1990
DOI: 10.1084/jem.172.3.673
|View full text |Cite
|
Sign up to set email alerts
|

Human eosinophils express transforming growth factor alpha.

Abstract: SummaryTransforming growth factor a (TGF-a) is a pleuripotential cytokine with diverse biological effects, including the ability to influence the proliferation of normal cells or neoplastic epithelial cells. Eosinophils are a subset of granulocytes that normally enter the peripheral tissues, particularly those beneath gastrointestinal, respiratory, and urogenital epithelium, where they reside in close proximity to the epithelial elements . In this study, we demonstrate that the great majority of eosinophils in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
73
0
3

Year Published

1991
1991
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 213 publications
(78 citation statements)
references
References 29 publications
2
73
0
3
Order By: Relevance
“…Because eosinophils (15) and airway epithelial cells such as NCI-H292 cells (27) are reported to produce TGF-␣, we examined the role of TGF-␣ in eosinophilinduced mucin synthesis. First, we found that activated eosinophils release TGF-␣.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because eosinophils (15) and airway epithelial cells such as NCI-H292 cells (27) are reported to produce TGF-␣, we examined the role of TGF-␣ in eosinophilinduced mucin synthesis. First, we found that activated eosinophils release TGF-␣.…”
Section: Discussionmentioning
confidence: 99%
“…Both eosinophils (15) and airway epithelial cells (27) can produce the EGFR ligand, TGF-␣. The present studies show that activated eosinophils secrete TGF-␣ and that a product of eosinophils also increases TGF-␣ expression in the epithelium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lineagespecific cytokine effects on differentiated cells, which retain hemopoietic cytokine receptors on their surface, result in "activation" or "phenotype switching": IL-3, IL-5, and GM-CSF can activate and prevent apoptosis of basophils and eosinophils (42,59); G-CSF and GM-CSF do the same for neutrophils (60). Autocrine stimulation by eosinophils, basophils, or mast cells of their own differentiation and/or activation is thus possible, since they produce a wide range of hemopoietic and proinflammatory cytokines, including IL-3, IL-4, IL-5, IL-6, and GM-CSF (33,(61)(62)(63)(64)(65)(66)(67)(68)(69).…”
Section: Cytokines and Lineage Specgcitymentioning
confidence: 99%
“…These diseases include asthma and the associated bronchial wall remodelling, and patients with a variety of interstitial pulmonary fibroses [16]. Indeed, there are now significant data demonstrating that eosinophils are important sources of a variety of pro-fibrogenic mediators, including: transforming growth factor (TGF)-a [17]; TGF-b [18]; vascular endothelial growth factor [19]; and type 2 cytokines, such as interleukin-13 [20]. When activated, eosinophils also release a variety of molecules that are toxic to the epithelium, including eosinophil cationic protein [21].…”
Section: Ap Shah Et Al Eosinophilic Lung Disease After Sjsmentioning
confidence: 99%